THE EXPRESSION OF NATIONAL IDENTITY IN ABDULLA QODIRIY’S NOVEL “SCORPION FROM THE ALTAR”: REALIA AND THEIR TRANSLATION INTO ENGLISH (Scientific journal of the Fergana State University, 2026)
This article examines linguocultural units that reflect the national identity of a given people — realia and their role in literary texts. In particular, it analyzes the realia found in Abdulla Qodiriy’s novel “Mehrobdan Chayon” and discusses the principles of their translation into English. The study also highlights the challenges faced by translators in rendering national and cultural elements during the translation process.